Development of conflict law in the United States of America - Chumachenko, Ivan Nikolaievich (Journal of the Belarusian State University. Law, 2021)
In the process of the formation of conflict law as a separate institution, the United States of America has passed a long way from the ideas of Samuel Livermore to the creation of a modern regulatory system, to which a large number of publications are devoted, as well as the recommendations of American Institute of Law. In this article, the author analyses the history and features of the formation of the modern system of US conflict law. The author elaborates and mentions the most notable works on the research topic, and also cites the latest publications of the draft restatement of the law, Third conflict of laws (as defined below) by the American Institute of Law, and also refers to the modern legislation of individual states, in particular, state of California. The author draws a conclusion about the originality of American conflict law, despite its European roots, as well as the flexibility, clarity and ease of understanding of the rules for resolving conflicts, which American legal scholars are trying to give to conflict law as part of the preparation of new restatement of the law, Third conflict of laws.